Diseño de una herramienta digital para la inspección y mantenimiento de casas con madera - Mora-Vicarioli, Lino (Instituto Tecnológico de Costa Rica, 2016)
In this paper is presented the Final Graduation project to achieve the degree of Licenciatura in Construction Engineer in Instituto Tecnológico de Costa Rica. Building systems in wood require higher level of professionalism, this can be achieved with the help of different tools to make the inspection of the construction progress. Also it is important to take advantage of these buildings, with a better maintenance they will have a longer useful life and it can prevent bigger damages. The main focus is the design and validation of a methodology for the inspection and maintenance of dwellings with building systems in wood. Such inputs are emerging as valuable resources for the field of construction engineering and related disciplines, specifically with the use from the wood. The manuals were made online by web an adaptative web site, it can be used in different electronical devices. Another advantage of using a digital format is that it makes easer the distribution of web link, the use of forms, easy upgrade and expansion of the resource so that new versions maintain the link to the user.
Proyecto de graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Viviendas; Construcciones en madera; Diseño y construcción; Mantenimiento preventivo; Inspección en obras